Visualization of the arterial valve morphology and number of leaflets in a fetus with common arterial trunk by spatiotemporal image correlation imaging - Mani Ram Krishna; Usha Nandhini Senniyan (Wolters Kluwer Medknow Publications, 2022)
Spatiotemporal imaging correlation (STIC) technology has been employed to visualize the fetal heart for close to two decades, but the additional value of the technology remains debatable. The value of the technology in identifying the morphology of the cardiac valves is being recognized. We report a 21-week gestational age fetus with common arterial trunk where STIC imaging enabled us to identify a bicuspid arterial valve.